Peningkatan Hasil Belajar Matematika Materi Penjumlahan Deret ke Samping Dua Bilangan Sampai 20 Melalui Media Game Interaktif pada Peserta Didik Disabilitas Fisik (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to improve the learning outcomes of students with physical disabilities in the subject of adding two numbers up to 20 using interactive games, while also improving the teaching process. The method used is Classroom Action Research (CAR) with a qualitative and quantitative approach. The study was conducted in two cycles, each consisting of four meetings. The research subjects included a third-grade teacher as the action implementer and two students with physical disabilities. Data were collected through observation, learning outcome tests, and documentation, then analysed descriptively. The results showed an increase in student learning outcomes in each cycle. At the beginning of the study, MG student achieved a score of 40% and AR student achieved a score of 50%. After the intervention in cycle I, learning outcomes increased to 60% for MG and 68% for AR. In cycle II, through the use of more targeted interactive games and the provision of rewards in the form of stickers, learning outcomes increased significantly to 84% for MG and 92% for AR. These findings indicate that interactive games are effective in improving mathematics learning outcomes in sideways addition for students with physical disabilities